Diversity, Abundance, and Niche Differentiation of Ammonia-Oxidizing Prokaryotes in Mud Deposits of the Eastern China Marginal Seas - Yu, Shaolan; Yao, Peng; Liu, Jiwen; Zhao, Bin; Zhang, Guiling; Zhao, Meixun; Yu, Zhigang; Zhang, Xiao-Hua (Frontiers in Microbiology, 2016)
The eastern China marginal seas are prominent examples of river-dominated ocean margins, whose most characteristic feature is the existence of isolated mud patches on sandy sediments. Ammonia-oxidizing prokaryotes play a crucial role in the nitrogen cycles of many marine environments, including marginal seas. However, few studies have attempted to address the distribution patterns of ammonia-oxidizing prokaryotes in mud deposits of these seas. The horizontal and vertical community composition and abundance of ammonia-oxidizing archaea (AOA) and bacteria (AOB) were investigated in mud deposits of the South Yellow Sea (SYS) and the East China Sea (ECS) by using amoA clone libraries and quantitative PCR. The diversity of AOB was comparable or higher in the mud zone of SYS and lower in ECS when compared with AOA. Vertically, surface sediments had generally higher diversity of AOA and AOB than middle and bottom layers. Diversity of AOA and AOB showed significant correlation with latitude. Nitrosopumilus and Nitrosospira lineages dominated AOA and AOB communities, respectively. Both AOA and AOB assemblages exhibited greater variations across different sites than those among various depths at one site. The abundance of bacterial amoA was generally higher than that of archaeal amoA, and both of them decreased with depth. Niche differentiation, which was affected by dissolved oxygen, salinity, ammonia and silicate (SiO32-), was observed between AOA and AOB and among different groups of them. The spatial distribution of AOA and AOB was significantly correlated with δ15NTN and SiO32-, and nitrate and δ13C, respectively. Both archaeal and bacterial amoA abundance correlated strongly with SiO32-. This study improves our understanding of spatial distribution of AOA and AOB in ecosystems featuring oceanic mud deposits.